The seventh link - Mayhew, Margaret, 1936- (Mayhew, Margaret, 1936- Village mystery., 2014)
The village of Frog End may be peaceful, but that doesn't mean that the Colonel's life there is quiet - not with his friendly but nosy neighbour Naomi, desperate to know what he's keeping in his new shed; the curious Miss Butler, who tracks his every move with her German U-boat captain's binoculars; and the attentions of the local vicar, who's keen to involve him in church affairs. That's not forgetting the demands of the aloof, imperious cat Thursday, who seems to have adopted the Colonel. So the Colonel is pleased when his old friend Geoffrey Cheetham invites him up to the village of Buckby for the weekend, to coincide with a RAF reunion event. After depositing an outraged Thursday at the Cat Heaven cattery, he drives up, and meets his fellow guests at the Cheethams' B&B: including a Lancaster bomber crew, reunited for the first time. But everything is not as it seems, and the Colonel finds himself taking on the reluctant role of sleuth once more when tragedy strikes.